2005
DOI: 10.1095/biolreprod.104.035626
|View full text |Cite
|
Sign up to set email alerts
|

Expression of α5 Integrin (Itga5) Is Elevated in the Rat Myometrium During Late Pregnancy and Labor: Implications for Development of a Mechanical Syncytium1

Abstract: The underlying mechanisms controlling uterine contractions during labor are still poorly understood. Integrins are heterodimeric, transmembrane receptors composed of alpha and beta subunits that can be found in focal adhesions. Because these structures play an important role in the regulation of smooth muscle contractility and cell adhesion, we hypothesized that alpha5 integrin mRNA (Itga5) and protein (ITGA5) expression would be induced in the rat myometrium during late pregnancy and labor. Itga5 mRNA express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 39 publications
0
43
0
Order By: Relevance
“…But, expression of both integrins and syndecans is known to be elevated in myometrium during late pregnancy and labor [Cluff et al, 2005;Williams et al, 2005], suggesting a possible role of focal adhesion signaling in the regulation of myometrial contractility. In the present study, we have linked gestation-dependent myometrial ERK targeting with focal adhesion signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But, expression of both integrins and syndecans is known to be elevated in myometrium during late pregnancy and labor [Cluff et al, 2005;Williams et al, 2005], suggesting a possible role of focal adhesion signaling in the regulation of myometrial contractility. In the present study, we have linked gestation-dependent myometrial ERK targeting with focal adhesion signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, FA have been postulated as mechano-sensors and sites for protein tyrosine kinase mediated signaling pathways [Burridge and Chrzanowska-Wodnicka, 1996]. However, few studies have been focused on this topic in the setting of pregnancy and labor [Macphee and Lye, 2000;Williams et al, 2005]. Studies from the Lye laboratory have suggested that endocrine pathways may not be sufficient alone to bring about myometrial activation for labor, and that additional pathways involving mechanical tension on the myometrium may also be involved [Macphee and Lye, 2000], but the signaling pathways linking mechanical forces to myometrial activation have not been delineated.…”
mentioning
confidence: 99%
“…Specific forward and reverse primers were designed using Primer Express software, version 2. (Williams et al 2005). Tubulin is present in almost all eukaryotic cells and is commonly used as a housekeeping protein (Vemuganti et al 2004).…”
Section: Western Immunoblot Analysismentioning
confidence: 99%
“…In human term pregnant myometrium, changes in cytoskeletal organization support a role for FAK and other focal adhesion-associated proteins as regulators of actin dynamics. Fibronectin receptor-alpha subunit (ITGA5) with its known partner ITGB1, is up-regulated in rat myometrium during late pregnancy and labor (Williams et al 2005) as well as vitronectin receptoralpha polypeptide (ITGAV) in the TNIL human myometrium (Rehman et al 2003). Therefore they may interact with actin-binding proteins (e.g.…”
Section: Focal Adhesion Adherens Junctions and Tight Junctionsmentioning
confidence: 99%